The reptile room - Snicket, Lemony; Helquist, Brett (New York : HarperCollins Publishers, 1999)
After narrowly escaping the menacing clutches of the dastardly Count Olaf, the three Baudelaire orphans are taken in by a kindly herpetologist with whom they live happily for an all-too-brief time.
AAL
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Humorous stories